2021
DOI: 10.1101/2021.03.26.21254369
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using Google Health Trends to investigate COVID-19 incidence in Africa

Abstract: Objectives: In the present manuscript we used Internet-derived data to assess whether Google Health Trends (GHT) search counts are able to track COVID-19 incidences in Africa. Methods: We collected COVID-19 case and death incidence for 54 African countries from February 2020 to January 2021. We used GHT to characterize COVID-19 incidence up to 24 January 2021, collecting the number of searches of four terms: coronavirus, coronavirus symptoms, COVID19, and pandemic. The terms were related to weekly COVID-19 c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Little to no research evaluate the predictive performance of models based upon GT data for African contexts. Internet penetration in Africa, compared with other continents, remains low, and such a study, therefore, represents a significant contribution (Fulk et al, 2021). Our preliminary results of the Spearman rank correlation analysis found that many (9 out of 15) search terms had significant contemporaneous correlations with the COVID-19 case numbers.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Little to no research evaluate the predictive performance of models based upon GT data for African contexts. Internet penetration in Africa, compared with other continents, remains low, and such a study, therefore, represents a significant contribution (Fulk et al, 2021). Our preliminary results of the Spearman rank correlation analysis found that many (9 out of 15) search terms had significant contemporaneous correlations with the COVID-19 case numbers.…”
Section: Discussionmentioning
confidence: 73%
“…Little to no research evaluate the predictive performance of models based upon GT data for African contexts. Internet penetration in Africa, compared with other continents, remains low, and such a study, therefore, represents a significant contribution (Fulk et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevention and surveillance remain crucial activities that have helped curb the spread of COVID-19. Another recommendation would be to anticipate outbreaks using a free internet tool Google Health Trends, as demonstrated by Fulk et al (2022).…”
Section: Discussionmentioning
confidence: 99%
“…Correlation with Google search queries has been investigated for vastly different medical conditions and in various clinical or population scenarios and settings, related and unrelated to reproductive health issues. [21][22][23][24][25] However, the correlation estimates that we quantified between search on Google about IUDs and actual IUD insertion rates is a new contribution to the evidence in this area. Related literature includes Guendelman et al 26 who showed US state policies on abortion could predict search volumes for abortion.…”
Section: Discussionmentioning
confidence: 99%